Insights into planktonic food-web dynamics through the lens of size and season - Carolina Giraldo; Pierre Cresson; Kirsteen MacKenzie; Virginie Fontaine; Christophe Loots; Alice Delegrange; Sébastien Lefebvre (Scientific Reports, 2024)
Abstract Knowledge of the trophic structure and variability of planktonic communities is a key factor in understanding food-web dynamics and energy transfer from zooplankton to higher trophic levels. In this study, we investigated how stable isotopes of mesozooplankton species varied seasonally (winter, spring, autumn) in relation to environmental factors and plankton size classes in a temperate coastal ecosystem. Our results showed that spring is characterized by the strongest vertical and size-structured plankton food-web, mainly fueled by the phytoplankton bloom. As a result, spring displayed the largest isotopic niche space and trophic divergence among species. On the contrary, both pelagic and benthic-derived carbon influenced low productive seasons (winter and autumn), resulting in more generalist strategies (trophic redundancy). Stable isotope mixing models were used to explore how different seasonal structures influenced the overall food web up to predatory plankton (i.e., mysids, chaetognaths, and fish larvae). Different feeding strategies were found in spring, with predators having either a clear preference for larger prey items (> 1 mm, for herring and dab larvae) or a more generalist diet (sprat and dragonets larvae). During low productive seasons, predators seemed to be more opportunistic, feeding on a wide range of size classes but focusing on smaller prey. Overall, the food-web architecture of plankton displayed different seasonal patterns linked to components at the base of the food web that shaped the main energy fluxes, either from phytoplankton or recycled material. Additionally, these patterns extended to carnivorous plankton, such as fish larvae, emphasizing the importance of bottom-up processes.